1984
DOI: 10.1084/jem.159.6.1604
|View full text |Cite
|
Sign up to set email alerts
|

T cell surface I-J glycoprotein. Concerted action of chromosome-4 and -17 genes forms an epitope dependent on alpha-D-mannosyl residues.

Abstract: Two genes acting in concert control murine T cell I-Jk expression. We determined I-Jk expression with I-Jk--specific monoclonal antibodies WF8 .C12.8 and five others produced in our laboratory in a cytotoxicity assay. Previous experiments established that an H-2k gene and a chromosome 4 gene, Jt , regulate I-Jk expression. We show here that B10. HTT and B10.S( 9R ) do not differ at the H-2k locus required for I-Jk expression. Rather B10. HTT , like B10.A(3R), lacks some important non--H-2 gene (possibly Jt ). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1985
1985
1986
1986

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…A role for I-J gene products is consistent with the ABA and NP systems (1, 3), but I-A and K/D restrictions have also been reported in other models (31)(32). Although a more complete definition of I-J gene products continues to evolve (1,34,35), their serologic presence and functional effect were clearly noted in the current study (Tables III, V, and XII). The target of the I-J restricted Ts-2 cell has yet to be established.…”
Section: Discussionsupporting
confidence: 87%
“…A role for I-J gene products is consistent with the ABA and NP systems (1, 3), but I-A and K/D restrictions have also been reported in other models (31)(32). Although a more complete definition of I-J gene products continues to evolve (1,34,35), their serologic presence and functional effect were clearly noted in the current study (Tables III, V, and XII). The target of the I-J restricted Ts-2 cell has yet to be established.…”
Section: Discussionsupporting
confidence: 87%
“…It has been reported that molecules of 36,000 and 24,000 daltons were precipitated from a culture supernatant ofTs with anti-I-J alloantiserum [29], but they were not well characterized. Another study showed that the I-J product is associated with a-D-mannosyl residues [30], Taniguchi et al [31] reported that the molecular weight of the I-J molecule was 24,000 daltons. Because SL-1 cells ex press a fairly large amount of the I-J antigen, a monoclonal antibody directed to I-J on SL-1 would be useful for studies of I-J molecules in the future.…”
Section: Discussionmentioning
confidence: 99%